Uji Koefesien Absorbsi Suara Serat Resam Dengan Matrik Polyester Sebagai Bahan Alternatif Peredam Suara - Napitupulu, Robert; Zakaria, Zakaria; Pranandita, Nanda (Manutech : Jurnal Teknologi Manufaktur, 2024)
Silencer is a tool to reduce the intensity of sound that occurs. Many have developed natural fibre-reinforced composite materials as an alternative to silencers, as they are considered more environmentally friendly than synthetic fibres and relatively cheaper. Resam plants are found in the Bangka Belitung area so that the availability is quite abundant. The purpose of this research is to test the sound absorption coefficient of resam fibre with polyester matrix as an alternative material for soundproofing. Making specimens using the hand lay-up method and research design using the full factorial method. The process variables used were volume fraction of 5%:95%, 10%:90%, 15%:85% and NaOH soaking time of 60, 90, 120 minutes and testing frequency of 500 Hz and 1000Hz. Based on the test results, the highest sound absorption coefficient was obtained in the variation of volume fraction of 15%: 85% volume fraction variation and the immersion time of NaOH solution for 90 minutes at a frequency of 500 Hz was 0.375. While the lowest sound absorption coefficient value in the variation of 5% volume fraction: 95% and the immersion time of NaOH solution for 90 minutes at a frequency of 1000 Hz was 0.16. Based on ISO 11654, the results obtained from this study, resam fibre filler composites can be used as an alternative sound absorbing material because it has exceeded the minimum value of 0.15.